2015
DOI: 10.1007/s11934-015-0526-6
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Replacement Therapy on the Natural History of Prostate Disease

Abstract: The physiology of testosterone production and action are closely related to prostatic disease. An understanding of the natural history of testosterone and prostate growth and development is needed in order to understand this complex relationship. Lower urinary tract symptoms (LUTS), benign prostatic hyperplasia (BPH), prostate cancer, and sexual function are common disorders for which testosterone is thought to play a role. Proposed in this review are some theories as to how testosterone interacts to potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 86 publications
0
9
0
1
Order By: Relevance
“…Benign Prostatic Hypertrophy/Lower Urinary Tract Symptoms Although a 2007 multinational physician survey revealed that up to 18% of providers considered benign prostatic hypertrophy (BPH) risk with T administration as very important, 112 no clinical trials demonstrate that TT worsens BPH/lower urinary tract symptoms. 113 No difference in prostatic androgens were found between men with and without BPH. 114 Placebo-controlled trials of exogenous administration of dihydrotestosterone (DHT) and T resulted in no changes in prostate DHT or T in blood sampling or prostate biopsy specimens.…”
Section: Prostate Cancermentioning
confidence: 93%
“…Benign Prostatic Hypertrophy/Lower Urinary Tract Symptoms Although a 2007 multinational physician survey revealed that up to 18% of providers considered benign prostatic hypertrophy (BPH) risk with T administration as very important, 112 no clinical trials demonstrate that TT worsens BPH/lower urinary tract symptoms. 113 No difference in prostatic androgens were found between men with and without BPH. 114 Placebo-controlled trials of exogenous administration of dihydrotestosterone (DHT) and T resulted in no changes in prostate DHT or T in blood sampling or prostate biopsy specimens.…”
Section: Prostate Cancermentioning
confidence: 93%
“…Androgens serve a critical role in prostate development, growth and pathogenesis. The use of 5ARIs and castration are effective therapies for BPH and prostate cancer, respectively ( 3 ). To investigate the variation of autophagy in human prostate epithelial cells under AD, a human prostate epithelial cell line, BPH-1, was used, which was cultured in a medium in which the androgens had been removed.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all males develop microscopic BPH by the age of 90 years ( 1 , 2 ). 5α-reductase inhibitors (5ARI) are able to reduce the concentration of dihydrotestosterone (DHT) in prostate tissue and thus shrink the prostate ( 3 ). Previous studies have revealed that normal prostatic epithelial cells responded to hormone deprivation by undergoing apoptosis ( 4 – 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other potential confounders of interest included history of testosterone replacement therapy,28 29 history of vasectomy,30 31 history of prostate inflammation/prostatitis,32 33 history of BPH diagnosis, treatment or procedure,34 history of bladder cancer, other urological cancers and hematuria 3536…”
Section: Methodsmentioning
confidence: 99%